You never forget your first? Impact of interview timing on institutional rank order. Issue 7 (18th April 2021) - Hanrahan, Brian; Lee, Christopher; Jozefowicz, Ralph; Schloemer, Fallon; Helms, Ann; Bradshaw, Deborah; Ojha, Ajithesh; Biswas, Sudipa; Carlson, Chad
Abstract: Objective: To analyze the impact of interview date on the applicant rank for Neurology residencies in the United States. Methods: A multi‐institutional retrospective review of interview dates and applicant rank list data for the National Resident Matching Program (NRMP) was conducted for five Neurology programs, totaling 1932 interviewed applicants over a combined total of 31 interview years. For each candidate, the interview date and applicant rank were abstracted along with the total number of interviews for that season. Statistical analyses were completed on the cumulative institution data set as well for each individual institution to assess for a possible relationship between interview date and applicant rank. Results: The cumulative institutional analysis showed that the mean applicant rank decreased as the interview season progressed. Applicants who interviewed on the first day of the interview season were ranked 11.4% higher than those who interviewed on the last interview day. Additionally, applicants interviewed on the first interview day more likely to be ranked higher when compared to all other interview dates. Independent analysis of each program's data identified comparable, statistically significant, differences in mean applicant rank and interview position at three out of the five institutions. Conclusions: This study evaluated the impact of interview order on the ranking of applicants by Neurology residency programs, noting a temporal relationship with applicant rank and interview date. The primacy bias appreciated in our data merits further evaluation in other medical specialties. Strategies to minimize the impact of this bias should be employed by residency programs who use medical matching services. Abstract : Hanrahan et al. examine 31 years worth of data from 5 residency programs and demonstrate a temporal relationship between interview date and applicant rank; earlier interviewees tend to rank higher.